Standardization Of Rakik Maco By Ulakan Tapakis Padang Pariaman - Wahidzal, Fajri; Andriani, Cici; Fridayanti, Lucy; Siregar, Juliana (Universitas Negeri Padang, 2024)
It was found that the quality of Rakik Maco differed from one seller to another. Like Rakik Maco's texture, some are fragile, some are tough and hard, some are thin and some are thick. In terms of color, there is Rakik Maco with a golden yellow color and a brownish yellow tone. In terms of taste, some are savory and some are bland. In processing Rakik Maco, sellers usually measure the ingredients using glass and some only look at the texture and viscosity of the dough, so the resulting quality varies, both in terms of texture, taste, aroma and color. Food quality is very important for Rakik Maco sellers to pay attention to. To maintain product quality, it is necessary to have appropriate standardization regarding the materials used, tools used and the process of making Rakik Maco.The focus of this research is the standardization of the Rakik Maco recipe in Ulakan Tapakis, Padang Pariaman Regency, which includes the measurements of ingredients and tools used, the manufacturing process and product quality (shape, color, aroma, texture and taste). To maintain product quality, standardization is necessary. Standardization is carried out regarding materials, tools and manufacturing processes. The quality of Rakik Maco can be seen from several aspects such as: shape, color, aroma, texture and taste. The following are the results of the Rakik Maco quality test: Rakik Maco has a thin round shape, with the use of a mold that makes Rakik Maco uniform and neat, the color of quality Rakik Maco is packaged yellow, the aroma of Rakik Maco is created from the distinctive aroma of rice flour and supported by the aroma of turmeric leaves , Rakik Maco has a crunchy texture, and Rakik Maco has a savory taste.